2004
DOI: 10.1161/01.atv.0000144951.08072.0b
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Increases LDL Oxidation and Expression of 15-Lipoxygenase-2 in Human Macrophages

Abstract: Objective-Macrophage-mediated oxidation of low-density lipoprotein (LDL) by enzymes, such as the lipoxygenases, is considered of major importance for the formation of oxidized LDL during atherogenesis. Macrophages have been identified in hypoxic areas in atherosclerotic plaques. Methods and Results-To investigate the role of hypoxia in macrophage-mediated LDL oxidation, we incubated human monocyte-derived macrophages with LDL under normoxic (21% O 2 ) or hypoxic (0% O 2 ) conditions. The results showed that hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 41 publications
(39 reference statements)
3
69
0
Order By: Relevance
“…9 In vitro studies have shown that low-density lipoprotein (LDL) uptake by macrophages is facilitated by a 2-step oxidation process, beginning with mild oxidation of lipid 10,11 followed by apolipoprotein B oxidation, a modification required for scavenger receptor recognition, which is unaffected by the cholesterol content of the cell. 12 Cultured macrophages exposed to oxidized LDL are richer in free cholesterol than cholesterol esters.…”
Section: Necrotic Core Enlargement Is Critical For Plaque Rupturementioning
confidence: 99%
“…9 In vitro studies have shown that low-density lipoprotein (LDL) uptake by macrophages is facilitated by a 2-step oxidation process, beginning with mild oxidation of lipid 10,11 followed by apolipoprotein B oxidation, a modification required for scavenger receptor recognition, which is unaffected by the cholesterol content of the cell. 12 Cultured macrophages exposed to oxidized LDL are richer in free cholesterol than cholesterol esters.…”
Section: Necrotic Core Enlargement Is Critical For Plaque Rupturementioning
confidence: 99%
“…Rydberg et al (19) showed that macrophages subjected to hypoxia in vitro up-regulate the expression of lipooxygenase-2, an enzyme implicated in low-density lipoprotein oxidation. In addition, hypoxia also up-regulates very low-density lipoprotein (VLDL) receptors on macrophages, and high levels of VLDL receptors are expressed by plaque macrophages in vivo (20,21).…”
Section: Atherosclerosismentioning
confidence: 99%
“…Macrophages present in arterial lesions are thought to be the principal mediators of LDL oxidation in the arterial wall [see review in ( 11 )]. Macrophage can modulate LDL oxidation through extracellular [ceruloplasmin ( 12 ), paraoxonase-1 ( 13 ), and myeloperoxidase ( 14 )] and intracellular ( 15,16 ), NADPH oxidase ( 17 ), LDL receptor-related protein 1 (LRP1) ( 18 ), and cytosolic phospholipase A 2 ␣ (cPLA 2 ␣ ) ( 19 )] mechanisms. Moreover, LDL oxidation by macrophages was recently reported to occur in the intracellular compartment within lysosomes ( 20 ).…”
Section: Rt-pcrmentioning
confidence: 99%